President McPhee in front of the new Administration Building (1942)
In 1942, a new Administration Building was completed near the site of Cal Poly's original 1903 administration hall. The clock tower of this building still stands and came to symbolize Cal Poly. Here President McPhee stands proudly in front of the new structure, which housed the president's office, the library, the State Bureau of Agricultural Education, deans' offices, classrooms, the print shop, and the student store.